Three-Dimensional Evaluation of the Effects of Different Treatment Methods on Pharyngeal Airways in Patients with Skeletal Class III Malocclusion - Mevlude Yuce Polat; İsmail Ceylan (Medicina)
Background and Objectives: The aim of this prospective study was to assess the effects of rapid maxillary expansion (RME) and/or face mask (FM) treatments on the pharyngeal airway in patients with skeletal Class III malocclusion caused by maxillary deficiency. This study utilized cone beam computed tomography (CIBT) for a three-dimensional (3D) analysis of airway changes, comparing the results with those of a control group consisting of untreated skeletal Class III patients. Materials and Methods: The study included 60 participants (34 boys, 26 girls) aged 9 to 14 years, all diagnosed with skeletal Class III malocclusion due to maxillary underdevelopment. The participants were divided into four treatment groups, each consisting of 15 individuals: Group 1—RME; Group 2—RME/FM; Group 3—FM; Group 4—Control group. The pharyngeal airway measurements were evaluated using CBCT and analyzed with Dolphin 3D software (version 11.9). Volumetric parameters and minimal axial area (MAA) were measured in the nasopharyngeal, retropalatal, retroglossal, and total airway regions. The collected data were statistically analyzed using SPSS 20.0 software. Results: The results indicated significant changes in pharyngeal airway volumes across all treatment groups compared to the control group. A statistically significant increase in nasopharyngeal, retropalatal, and total airway volume were observed in all treatment groups. Only the RME group demonstrated a significant increase in retroglossal volume. Significant increases in MAA were found in the RME/FM and FM groups in the nasopharyngeal and retropalatal regions. However, minimal changes were observed in the retroglossal region across all treatment groups. The control group showed no significant changes in any of the measured parameters, underscoring the effects of the treatments. Conclusions: The findings of this study suggest that both RME and/or FM treatments result in significant positive changes in the pharyngeal airways, particularly in the nasopharyngeal and retropalatal regions. The retroglossal region showed more limited response to the treatments. The combined RME/FM therapy was found to be particularly effective in improving airway dimensions in the anterior and mid-pharyngeal regions. These results highlight that early orthodontic interventions, such as RME and FM, can improve both airway patency and overall respiratory function, in addition to addressing skeletal Class III malocclusion.